Dose-dependence of dietary antioxidants in their biological actions for research in human chronic diseases - Lestari, Widya; Jaswir, Irwandi; Nordin, Nur Sazwi; Octavianti, Fitri; Nagao, Akihiko (2014)

(untitled)
Dietary antioxidants are substances in foods that significantly decrease the adverse effects of reactive oxygen species, reactive nitrogen species, or both on normal physiological function in humans. Mostly found in fruits and vegetables, they prevent free radicals from attacking cells and damaging DNA. Epidemiological evidences have suggested that intake of fruits and vegetables reduces the risk of both cancer and cardiovascular disease. Flavonoids, carotenoids, vitamin C, vitamin E and selenium are the major dietary antioxidants. Several large intervention studies have thus been conducted with beta-carotene and vitamin E, leading investigations on chemoprevention of chronic diseases with dietary antioxidants. However, beta-carotene supplementation has shown not only positive but also negative effects on human health. The antioxidant activity of these compounds may shift into prooxidant activity, depending on the redox potential of the carotenoid molecules as well as on the biological environment in which they act. The prooxidant potency of these compounds is determined by several factors, including oxygen tension, carotenoid concentration, and interactions with other antioxidants. Prooxidant activity can induce harmful results in biologic systems and influence the development of human chronic diseases.